PENGARUH PENDIDIKAN CEO, GENDER CEO, USIA CEO, DAN NARSISME CEO TERHADAP MANAJEMEN LABA (Studi Empiris Terhadap Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019) - Nurbaity Cahya; Nur DP Emrinaldi; Mela Fito Nanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of CEO education, CEO gender, CEO age, and CEO narcissism on earnings management. The modified Jones model is used to measure the dependent variable, namely earnings management. The independent variable CEO education is measured by giving a score of 1-5 for the level of education of the CEO, the dummy variable is used to measure the gender variable of the CEO, the age of the CEO is measured using the age of the CEO, and the narcissism of the CEO using the measurement gives a score of 1-4 on the CEO's photo. in the company's annual report. The population in this study were 154 manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 so that from this population a sample of 37 companies was obtained using the purposive sampling method. The data analysis technique used in this study is multiple linear regression analysis. The results showed that CEO gender had a significant effect on earnings management. Meanwhile, CEO education, CEO age, and CEO narcissism have no significant effect on earnings management.Keywords: CEO education, CEO gender, CEO age, CEO narcissism, and earnings management